Hydrogels in the Treatment of Degenerative Tendinopathy - Subervier Ortiz, Laura; Villanueva-Ibáñez, Maricela; Jaramillo Loranca, Blanca Estela; Bojalil Parra, Rafael (Revista Mexicana de Ingenieria Biomedica, 2023)
Degenerative tendinopathy is a significant health problem, and its incidence increases yearly. This condition causes functional deficits in young and adult patients and sedentary or active individuals, resulting in health, social, and economic consequences. Due to limited blood supply, drug administration is complex for tendon diseases, such as degenerative tendinopathy. Biomaterials, such as hydrogels, have gained significant attention in designing drug delivery systems to treat musculoskeletal pathologies due to their attractive characteristics and the challenges posed by conventional drug delivery routes. This paper provides an overview of tendon pathology and discusses the use of hydrogels as drug carriers and release agents in emerging treatments.